Board Structure, CEO Tenure, Firms’ Charactersitics and Performance of Financial Institutions in Kenya - Nebert Mandala; Erasmus Kaijage; Josiah Aduda; Cyrus Iraya (European Scientific Journal, ESJ, 2017)
The broad objective of this research was to determine the effect of board structure on the performance of financial institutions in Kenya and also to find out what the intervening and mediating influence of the tenure of the CEO and firm’s characteristics on this relationship might be. The specific objectives included; to examine the influence of board structure on performance of financial institutions in Kenya; to determine the intervening influence of CEO tenure on the association among board structure and performance of financial sector firms in Kenya; to examine the moderating effect of the firms’ characteristics on the association among board structure and performance of financial institutions in Kenya; and to ascertain the joint effect of board structure, CEO tenure and firms’ characteristics on performance. Secondary data was collected for a ten-year period from 2006 to 2015. Moderated and stepwise regression models and correlation analysis were adopted for the investigation of the association among the variables. The results showed that board structure had independent significant influence on performance of financial institutions; there was no significant intervening effect of CEO tenure on this relationship; there was a significant moderating effect of firms’ characteristics on the relationship; and the joint effect of board structure, CEO tenure and firms’ characteristics was significant. Through this study, the formulation of managerial policies and practices which will promote better governance practices and also appropriate the characteristics of firms and that will improve performance of financial institutions will be enhanced.